2017
DOI: 10.1210/jc.2017-02068
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Suppression of Luteinizing Hormone Pulse Frequency in Adolescent Girls With Hyperandrogenism: Effects of Metformin

Abstract: Short-term metformin use improved biochemical hyperandrogenemia, but did not improve hypothalamic sensitivity to P4 suppression, in adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The decrease in the expression of progesterone receptor was observed [ 78 ]. This finding of the impaired progesterone feedback was shown in the study, in which the women afflicted by PCOS required higher levels of progesterone to decrease the LH level, as compared to the women without PCOS [ 79 ].…”
Section: Potential Drug Targets and Active Substances In Novel Thementioning
confidence: 63%
“…The decrease in the expression of progesterone receptor was observed [ 78 ]. This finding of the impaired progesterone feedback was shown in the study, in which the women afflicted by PCOS required higher levels of progesterone to decrease the LH level, as compared to the women without PCOS [ 79 ].…”
Section: Potential Drug Targets and Active Substances In Novel Thementioning
confidence: 63%
“…The PCOS group in our study was under treatment with metformin. It has been shown that metformin improves not only insulin resistance but also biochemical hyperandrogenemia [40]. No data exist regarding the effect of oral contraceptives on the body composition of lean PCOS patients, but in menopausal females, OCs seem to induce muscle anabolism [41].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced hypothalamic sensitivity to progesterone negative feedback on LH secretion also is a hallmark of PCOS women (Chhabra et al 2005) and is similarly restored with flutamide (Eagleson et al 2000, Chhabra et al 2005. Comparable neuroendocrine abnormalities are found in adolescent hyperandrogenic girls, likely representing a precursor to adult PCOS (Lundgren et al 2018). Moreover, PCOS women show a sexually dimorphic pattern of exaggerated early LH responsiveness to GnRH analog that more closely resembles that of men or women with congenital adrenal virilizing disorders (e.g., classical CAH and adrenal virilizing carcinoma) than normal women (Rosenfield et al 1990, Barnes et al 1994.…”
Section: Neuroendocrine Dysfunctionmentioning
confidence: 99%